2012
DOI: 10.1002/jmr.2221
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐binding energetics of human α‐1‐acid glycoprotein assessed by isothermal titration calorimetry and molecular docking simulations

Abstract: This study utilizes sensitive, modern isothermal titration calorimetric (ITC) methods to characterize the microscopic thermodynamic parameters that drive the binding of basic drugs to α-1-acid glycoprotein (AGP) and thereby rationalize the thermodynamic data in relation to docking models and crystallographic structures of the drug-AGP complexes. The binding of basic compounds from the tricyclic antidepressant series, together with miaserine, chlorpromazine, disopyramide and cimetidine all displayed an exotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…The low stoichiometric ratio is also observed for Wrf, which has been reported to exhibit phenotype selectivity and to possess a stronger binding with the S-enantiomer for F1*S (Nakagawa et al, 2003). The enthalpyentropy compensation observed in our CAPs binding data is consistent with the thermodynamic data for basic small-molecule drugs recently reported by Huang et al, 2012. The low stoichiometric ratio observed in our binding data is however not previously described and thus differs from the small-molecule study.…”
Section: Isothermal Titration Calorimetrysupporting
confidence: 88%
See 2 more Smart Citations
“…The low stoichiometric ratio is also observed for Wrf, which has been reported to exhibit phenotype selectivity and to possess a stronger binding with the S-enantiomer for F1*S (Nakagawa et al, 2003). The enthalpyentropy compensation observed in our CAPs binding data is consistent with the thermodynamic data for basic small-molecule drugs recently reported by Huang et al, 2012. The low stoichiometric ratio observed in our binding data is however not previously described and thus differs from the small-molecule study.…”
Section: Isothermal Titration Calorimetrysupporting
confidence: 88%
“…The larger polymyxin antibiotics display a cyclic nonapeptidic backbone carrying several positive charges and are thus related to the shorter peptides studied in the present report even though the CAPs display an overall exothermic binding to AGP. The comprehensive small molecule study shows that ligands may bind to both AGP phenotypes with the same affinity, although the orientation of the bound molecule may differ as shown for chlorpromazine binding (Huang et al ., ). Whether this is possible for the larger CAPs was not established.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The a1-acid glycoprotein, an acute phase protein, is the principle extracellular lipocalin that plays an important role in the transport of hydrophobic compounds [22,23]. It is reported that a1-acid glycoprotein increases in HF patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen atoms were then added to the protein, and the structures of protein, ligand, and cofactor were combined in a single Macromodel file. The hydrogen atoms were minimized for 1000 steps with Macromodel in OPLS-AA force field, with all nonhydrogen atoms constrained to their original positions 13 . C. Docking Studies: The ligand-macromolecule interaction conformation is predicted and scored in terms of binding free energy between the ligand and macromolecule, have made a remarkable progress in their accuracy and speed, although molecular docking is an extremely demanding task for computer resources.…”
Section: A Finding Target Active Site and Ligandmentioning
confidence: 99%